Scoping Review: Antenatal Knowledge on Breastfeeding Preparation Among Pregnant Women - Fitriani, Desiy; Rukmana, Siti (Papua Medicine and Health Science, 2025)
Pregnant women play a vital role within the community in assessing the factors that influence future breastfeeding success. Breast milk is the most optimal source of nutrition for infants and provides significant health benefits for both mother and child. According to the World Health Organization (WHO), exclusive breastfeeding is recommended for the first six months of life, followed by the introduction of complementary foods between five and seven months. However, breastfeeding practices often do not align with these recommendations. A mother's success in exclusive breastfeeding is strongly influenced by family support, which can significantly enhance her confidence. Objective: This study aims to analyze breastfeeding patterns among primiparous mothers in order to improve the forms of support provided to them. Methods: This scoping review was conducted using the framework developed by Arksey and O'Malley. Results: Based on five selected articles, two used cross-sectional designs, one was a descriptive study, one used qualitative data, and one employed Chi-square analysis. The findings revealed that comprehensive prenatal knowledge significantly improves maternal self-efficacy in the breastfeeding process. Conclusion: Pregnant women's knowledge and attitudes toward breastfeeding remain insufficient, as does their intention to breastfeed optimally. These findings highlight the need for culturally tailored interventions to improve knowledge, attitudes, and intentions regarding breastfeeding, thereby supporting better future breastfeeding practices for their children.